a)
\(\frac{4}{x-5}+\frac{9}{x+5}=\frac{1}{2}\\ \Leftrightarrow\frac{4x+20}{2\cdot\left(x^2-25\right)}+\frac{9x-40}{2\cdot\left(x^2-25\right)}-\frac{x^2-25}{2\cdot\left(x^2-25\right)}=0\\ \Leftrightarrow\frac{4x+20+9x-40-x^2+25}{2\cdot\left(x^2-25\right)}=0\\ \Leftrightarrow\frac{13x+5-x^2}{2\cdot\left(x^2-25\right)}=0\\ \Rightarrow13x+5-x^2=0\\ \Rightarrow x=\left[{}\begin{matrix}-\frac{-13+3\sqrt{21}}{2}\\-\frac{-13-3\sqrt{21}}{2}\end{matrix}\right.\)
b)
\(x^4-4x^2+3=0\\ \Leftrightarrow\left(x^2-3\right)\cdot\left(x^2-1\right)=0\\ \Rightarrow x=\left[{}\begin{matrix}\sqrt{3}\\-\sqrt{3}\\1\\-1\end{matrix}\right.\)
Bài làm
a) \(\frac{4}{x-5}+\frac{9}{x+5}=\frac{1}{2}\) ĐKXĐ: x khác 5, x khác -5
\(\Rightarrow2.4.\left(x+5\right)+9.2\left(x-5\right)=2\left(x+5\right)\left(x-5\right)\)
\(\Leftrightarrow8x+40+18x-90=2x^2-50\)
\(\Leftrightarrow-2x^2+26x=0\)
\(\Leftrightarrow2x\left(-x+13\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x=0\\-x+13=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=13\end{matrix}\right.\)( tmđkxđ )
Vậy S = { 0; 13 }
b) x4 - 4x2 + 3 = 0
<=> x4 - x2 - 3x2 + 3 = 0
<=> x2( x2 - 1 ) - 3( x2 - 1 ) = 0
<=> ( x2 - 3 )( x2 - 1 ) = 0
\(\Leftrightarrow\left[{}\begin{matrix}x^2-3=0\\x^2-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\pm\sqrt{3}\\x=\pm1\end{matrix}\right.\)
Vậy S = { 3; -3; 1; -1 }